2018
DOI: 10.1371/journal.pone.0200410
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the bioelement content of summer and winter western honeybees (Apis mellifera) induced by Nosema ceranae infection

Abstract: Proper bioelement content is crucial for the health and wellness of all organisms, including honeybees. However, the situation is more complicated in these important pollinators due to the fact that they change their physiology during winter in order to survive the relatively harsh climatic conditions. Additionally, honeybees are susceptible to many diseases such as nosemosis, which during winter can depopulate an entire colony. Here we show that summer bees have a markedly higher content of important bioeleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…The pollinator fidelity hypothesis suggested that so-called “toxic nectar” is analogous to other floral structures that require specialisation of pollinators [ 24 , 73 , 74 ]. Honeybees taking such herb nectar might self-heal slightly or weakly infected colonies [ 15 , 17 ]. We bring out this hypothesis here because nectars rich in specific secondary compounds can decidedly benefit honeybees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pollinator fidelity hypothesis suggested that so-called “toxic nectar” is analogous to other floral structures that require specialisation of pollinators [ 24 , 73 , 74 ]. Honeybees taking such herb nectar might self-heal slightly or weakly infected colonies [ 15 , 17 ]. We bring out this hypothesis here because nectars rich in specific secondary compounds can decidedly benefit honeybees.…”
Section: Discussionmentioning
confidence: 99%
“…neumanni, was described in 2017 [ 12 ]. Nosemosis negatively alters the gut epithelium renewal rate [ 13 ] and creates a layer of mature spores on the intestine surface [ 14 ], which leads to bee malnutrition and changes in the composition of microelements [ 15 ]. Nosemosis also changed honeybee intestinal microbiome contents, both on bacterial [ 16 ] and yeast [ 17 ] levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chambers were located inside the aluminum block. The volume of chambers designed for TGS8xx sensors was about 12 cm 3 and volume of chambers for TGS2xxx sensors was about 4 cm 3 .…”
Section: Measurement Device Based On Gas Sensorsmentioning
confidence: 99%
“…The honey bee population has strongly declined in recent years [1] due to a combination of multiple stresses, including diseases, pathogens and pesticides. Bees, like all animals including humans, are susceptible to viruses (e.g., deformed wing virus, Israeli acute paralysis virus, Kashmir bee virus, Black Queen cell virus and Sacbrood); bacteria (e.g., American foulbrood and European foulbrood); fungi (e.g., Chalkbrood and Stonebrood); microsporidian parasite (e.g., Nosema apis and Nosema cearanae); parasitic mites (e.g., Tracheal mites (Acarapis woodi), Varroa mites, and Varroa mites resistant to fluvalinate and coumaphos); and insect pests (e.g., wax moth, and small hive beetle) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%